Financial inclusion with hybrid organisational forms: Microfinance, philanthropy, and the poor law in Ireland, c. 1836-1845 - Eoin McLaughlin; Rowena A. Pecchenino (Queen's University Centre for Economic History (QUCEH), 2020)
The turbulent 1830s saw a sequence of great political and social reforms in the UK. One such reform was the introduction of a locally funded poor law in Ireland. The development of a nascent welfare system in 1838 coincided with a boom in the formation of microfinance institutions in Ireland. The focus of this study is the expansion of a hybrid organisational form, Loan Fund Societies (LFSs), in the ten years prior to the Great Irish Famine of 1845-49. LFSs were legally established with a conflictual structure: balancing acting as commercially viable charitable institutions that were required to provide credit to the deserving poor to enable them to be self-sufficient, while dedicating their "profits" to supporting the indigent poor. This study uses an analytical framework drawing inspiration from institutional logics to explore and better understand Irish microfinance in the early nineteenth century, a period of profound socio-economic and socio-religious change. It seeks to explain the factors that motivated the establishment and de-establishment of microfinance institutions amidst this tumult. Legislative changes in LFS business parameters in 1843 made the tensions between being charitable and commercial sustainability salient and, for some, continued existence untenable.
Keywords: G21; H75; I38; N23; N33; N83; 330; microfinance; institutional logics; development; Ireland